Knowledge and habits of solar exposure in street traders of a market in Chiclayo, Peru: Conocimientos y hábitos de exposición solar en comerciantes ambulantes de un mercado de Chiclayo, Perú - Sempértegui-Ruiz, Sherly Raquel (2020)
Background: people who work outdoors are exposed to long periods of ultraviolet radiation; such is the case of street vendors. Objectives: determine the knowledge and habits of solar exposition in itinerant traders around a Chiclayo market. Materials and methods: A questionnaire were applied to 291 itinerant merchants located around the Mercado Modelo of Chiclayo, who evaluated sun exposure habits, photo protection measures, a history of sunburn and skin cancer, as well as knowledge of ultraviolet radiation and sources of information. Results: the following results were found: the age ranges were 18-25 (42.3%), 36-54 (38.1%), 55 -78 (19.6%). At the level of education, 13.1% have completed primary school, 32.6% have full secondary and 8.2% complete. At the time of the study, 71.9% had been working as street traders for more than 3 years. The phototype of the participants were phototype I (0.3%), phototype II (4.5%), phototype III (24.7%), phototype IV (48.8%), phototype V (19.6%), phototype VI (2.15). A 90 ± 3.5 %% recognizes that causes skin cancer, 53.6% recognizes that a feature of skin aging by radiation are spots and warts, 56% responded that solar radiation causes cataracts, a 52,92 % replied that white-skinned people are more sensitive to the sun's rays. 59.5% of traders indicated that they go to work from Monday to Sunday, 39.4% work 5-6 days a week, and 4.1% work 4 or less days a week. A 48.5% of them declared to expose themselves more than 6 hours to the solar rays, 24.7% are exposed of 3 - 6 hours a day, while 8.6% registered the shortest time of solar exposure (0 - 2 hours). 75.3% did not use sunscreen, 24.7% of merchants used sunscreen at the time of being surveyed as a measure of photo protection; of them, 63.9% said that a family member recommended their use, 94.4% use it 1-2 times a day, 38.9% only apply it when they go to work, 52.8% use it on their face , neck, ears and hands, and half of them (50.0%) get it from a catalog. Conclusions: the knowledge and habits of solar exposition in itinerant traders were equal or inferior to that described in other studies. It was found that the knowledge is from regular to adequate and poor habits.